Validation Of Analysis Method For Determining Content Of Chlorpheniramine Malate (Ctm) In Tablet Preparation By Uv Spectrophotometry - Sa'adah, Anifatus (Science and Community Pharmacy Journal, 2023)
Abstract: In the pharmaceutical industry, quality control of a medicine is one part of Good Medicine Manufacturing Practices (CPOB) which is used to ensure that the product has quality that is appropriate for its intended use, so that the production results marketed meet the CPOB requirements. Therefore, this study aims to determine the levels of the active substance chlorpheniramine maleate (CTM) in drug samples and compare them with standards using UV spectrophotometry. The research results showed that the maximum CTM wavelength measurement obtained was 263 nm. The linear equation y = 0.01904x + 0.03139 with a correlation coefficient (R) value of 0.995. The SD obtained by sample A was 0.4483 and the % relative standard deviation (%RSD) value was 14.6%, sample B was 0.2020 and the % relative standard deviation (%RSD) value was 6.4%, sample C was 0.0542 and the % relative standard deviation (%RSD) value is 1.3%. The LOQ values obtained on samples A, B and C are not accepted as quantitation limits because they do not meet precision (CV < 20%) and accuracy (bias < ±20%). The average % recovery results obtained for samples A, B, and C were 100%. The range of CTM levels obtained was 159.307%, 145.025%, and 126.195%. Keywords: UV Spectrophotometry, Chlorpheniramine maleat, Validation of analytical methods